Managing end-of-life care in Malaysia: The economic considerations from the ethical and Islamic perspectives - Alias, Fadhlina; Jahn Kassim, Puteri Nemie; Mohamad Hussain, Mazlena (International Institute of Islamic Civilisation and Malay World (ISTAC), 2019)
Since the turn of the 20th century, the increase in the degree of medical prevalence particularly at the end of life, has redefined the dimensions between life and death. Medical treatment and equipment are now able to prolong the life expectancy of patients suffering from life-limiting illnesses even in the absence of any brain activity. This has impacted upon the delivery of end-of-life care, which focuses on providing a comfortable environment for patients who are suffering from incurable diseases and for whom death is imminent. The emergence of sophisticated medical devices and interventions has raised ethical issues relating to end-of-life decisions especially in withholding or withdrawing life sustaining treatments. In such a situation, economic considerations constitute an important factor in the provision of end-of-life care due to the costly and limited resources which are required for providing such life-sustaining treatment. Healthcare providers need to grapple with issues justifying resource allocation amongst patients, which are in turn contingent upon deliberations on medical futility. This paper seeks to discuss the economic considerations involved in the management of end-of-life care from the ethical and Islamic standpoints and ultimately, to provide recommendations for the promotion of a comprehensive national policy that is suitable and viable for the Malaysian healthcare environment.